Understanding Transactive Memory Systems (TMS) in Tourism Information Sharing - Virginia Mandasari; Nurkholish Majid (Nusantara Science and Technology Proceedings, 2022)
This study aims to investigate the phenomenon of sharing information in social media groups. This research also investigates the role that communication plays in the dissemination of information within groups and the formation of self-relevant values. The methodology was quantitative, and the sampling method was purposive. Using a survey to collect information from 807 students at SMAN 18 Bandung. In the analysis data section, the proposed model was evaluated utilizing Structural Equation Modeling (SEM). The model proposed was evaluated using AMOS 21. The model's fit indices demonstrate good fit. There are five accepted hypotheses in this study. It was discovered that 1) formal and 2) informal communications have a positive impact on transactive memory systems, 3) transactive memory systems have a positive impact on self-relevant value, and 4) transactive memory systems are an effective mediator between formal and informal communication and self-relevant value. The study suggests some strategic implications as well.